Determination of user experience on food business websites by using Neuromarketing techniques - Erhan Babaç; Hilmi Rafet Yüncü (Tourism & Management Studies)
In this research, the relevant literature was scanned and 28 items about visual contents were removed from the literature. With these items, the needs assessment analysis was performed by applying the Delphi technique, on eight experts who constitute the subjects of the study at the same time. In the next stage of the research, two websites were created based on the visual content items extracted from the literature and presented to experts with the Delphi technique. By creating the experimental procedure, an experimental area was prepared for eight subjects, and websites were shown to them. EEG and eye-tracking measurements were made over the websites that were shown during the experiment. The data obtained from the EEG are over Alpha, Beta-1, and Beta-2 frequencies, and revealed respectively attention, high concentration, and anxiety. The total number of fixations based on eye-tracking data was measured synchronously with the EEG data. Findings revealed that the experiment1 website, which was used visual content, was a more efficient website on attention, high concentration, and total fixation. The anxiety level of the experiment2 website was more perceptible to the subjects.